Teachers’ Attitudes Towards Educating Talented Students and Their Predictors - Teresa Giza; Justyna Bojanowicz (Studia z Teorii Wychowania)
From the perspective of the trajectory of talents development at subsequent stages of education, students require different teachers and different types of support. The positive attitudes of teachers towards educating talented students are the issues that do not change. The purpose of the article is to present the results of studies on teachers’ attitudes and to determine their predictors. The Scale of Teachers’ Attitudes Towards Educating Talented/Gifted Students (STATETS) questionnaire (N=127) was used in the studies. The largest percentage of respondents showed a pro-ability social attitude (40.9%), while anti-ability and pro-ability methodical attitudes were shown by approximately 30% of respondents each. The gender, social environment and experience in working with talented students turned out to be variables differentiating attitudes. The analysis of latent profiles allowed us to distinguish three groups of teachers: with a dominant anti-ability attitude (11 people), with a dominant methodological attitude (11 people) and the largest group, in which the intensity of the three attitudes was equal (105 people). The analysis did not show any significant relationships between sociodemographic variables and the distinguished profiles. The studies have theoretical significance in terms of the typology of teachers’ attitudes and their predictors, and practical significance – for the area of teacher education.